Attention Capture of Non-target Emotional Faces: An Evidence From Reward Learning - Zhou, Xing; Du, Bixuan; Wei, Zhiqing; He, Weiqi (Frontiers in Psychology, 2020)
The aim of this study was to investigate whether emotional faces act as distracters and cause preferential processing during tests after reward learning. In the current study, using a visual search paradigm we examined how reward training affect emotion attention processing. The emotional face appeared as a task-irrelevant distracter during the test after reward learning, and participants were asked to judge the orientation of a line on the face. The results showed that when an emotional face appeared as a distracter after reward learning, the response to both happy and fearful faces under high-reward condition was significantly slower than the response under low-reward condition. The response to fearful face under high-reward and low-reward conditions was slower than the response to other emotions, but there was no significant difference between the response times to fearful face and neutral face under high-reward condition. The results reveal that reward learning has substantial influence on emotional attention processing, especially high reward weakens the processing advantage on fearful faces.